Sleep, Aging, and Cellular Health: Aged-Related Changes in Sleep and Protein Homeostasis Converge in Neurodegenerative Diseases - Hafycz, Jennifer M.; Naidoo, Nirinjini N. (Frontiers in Aging Neuroscience, 2019)
Many neurodegenerative diseases manifest in an overall aged population, the pathology of which is hallmarked by abnormal protein aggregation. It is known that across aging, sleep quality becomes less efficient and protein homeostatic regulatory mechanisms deteriorate. There is a known relationship between extended wakefulness and poorly consolidated sleep and an increase in cellular stress. In an aged population, when sleep is chronically poor, and proteostatic regulatory mechanisms are less efficient, the cell is inundated with misfolded proteins and suffers a collapse in homeostasis. In this review, we explore the interplay between aging, sleep quality, and proteostasis and how these processes are implicated in the development and progression of neurodegenerative diseases like Alzheimer’s disease. We also present data suggesting that reducing cellular stress and improving proteostasis and sleep quality could serve as potential therapeutic solutions for the prevention or delay in the progression of these diseases.